Polydopamine Nanocluster Embedded Nanofibrous Membrane via Blow Spinning for Separation of Oil/Water Emulsions - Zhenglian Liu; Ziling Xu; Chaoqi Liu; Yajing Zhao; Qingyin Xia; Minghao Fang; Xin Min; Zhaohui Huang; Yan’gai Liu; Xiaowen Wu (Molecules, 2021)
Developing a porous separation membrane that can efficiently separate oil–water emulsions still represents a challenge. In this study, nanofiber membranes with polydopamine clusters polymerized and embedded on the surface were successfully constructed using a solution blow-spinning process. The hierarchical surface structure enhanced the selective wettability, superhydrophilicity in air (≈0°), and underwater oleophobicity (≈160.2°) of the membrane. This membrane can effectively separate oil–water emulsions, achieving an excellent permeation flux (1552 Lm−2 h−1) and high separation efficiency (~99.86%) while operating only under the force of gravity. When the external driving pressure was increased to 20 kPa, the separation efficiency hardly changed (99.81%). However, the permeation flux significantly increased to 5894 Lm−2 h−1. These results show that the as-prepared polydopamine nanocluster-embedded nanofiber membrane has an excellent potential for oily wastewater treatment applications.